Intake of fruits and vegetables according to pesticide residue status in relation to all-cause and disease-specific mortality: Results from three prospective cohort studies. (15th January 2022) - Sandoval-Insausti, Helena; Chiu, Yu-Han; Wang, Yi-Xin; Hart, Jaime E.; Bhupathiraju, Shilpa N.; Mínguez-Alarcón, Lidia; Ding, Ming; Willett, Walter C.; Laden, Francine; Chavarro, Jorge E.
Graphical abstract: Highlights: High-pesticide-residue FV intake is unrelated to mortality. Low-pesticide residue FV intake is inversely related to mortality. Exposure to pesticide residues through diet may offset the beneficial effect of FV intake on mortality. Additional evaluation is particularly important for respiratory disease mortality. Abstract: Background: Intake of conventionally grown fruits and vegetables (FVs) is an important route of exposure to pesticide residues in the general population. However, whether health risk stemming from exposure to pesticides through diet could offset benefits of consuming FVs is unclear. Objective: We assessed the association of FV intake, classified according to their pesticide residue status, with total and cause-specific mortality. Methods: We followed 137, 378 women (NHS, 1998–2019, and NHSII, 1999–2019) and 23, 502 men (HPFS, 1998–2020) without cardiovascular disease, cancer, or diabetes at baseline. FV intake was assessed using validated food frequency questionnaires and categorized as having high- or low-pesticide-residues using data from the USDA Pesticide Data Program. Cox proportional hazards models were used to estimate hazard ratios (HRs) and 95% confidence intervals (CI) for total and cause-specific mortality associated with high- and low-pesticide-residue FV intake. Results: A total of 27, 026 deaths, including 4, 318 from CVD and 6, 426 from cancer, were documented during 3, 081, 360 person-years of follow-up. In multivariable-adjusted analyses, participants who consumed ≥4 servings/day of low-pesticide-residue FVs had 36% (95% CI: 32%-41%) lower mortality risk compared to participants who consumed <1 serving/day. The corresponding estimate for high-pesticide residue FV intake was 0.93 (95% CI: 0.81–1.07). This pattern was similar across the three most frequent causes of death (cardiovascular disease, cancer and respiratory diseases). Conclusions: High-pesticide-residue FV intake was unrelated whereas low-pesticide residue FV intake was inversely related to all-cause mortality, suggesting that exposure to pesticide residues through diet may offset the beneficial effect of FV intake on mortality.